Concept design of a digital twin architecture for ship structural health management. Issue 1 (1st July 2022) - Cheng, Zhiping; Tan, Eric; Cai, Minbo; Magee, Allan Ross
Abstract: Ocean-going vessels frequently experience severe weather conditions. Occasionally, the actual environmental loads are much larger than design values, resulting in deviations from design conditions that may cause serious structural damage. A structural digital twin can enhance predictability and reliability of marine structures, and thus provide vessel operators, owners, and stakeholders with a more accurate overview of a vessel's condition. It can also help reduce lifecycle costs through proposing rational and optimal inspection, maintenance, repair programs, and assist on maximizing service life and mission availability. This paper uses a benchmark vessel to investigate structural behaviors of the vessel through dynamic loading approach. The correlation between structure members and critical responses are established, and high stress concentration areas have been identified. Subsequently, this paper develops a conceptual digital twin architecture. The proposed digital twin predicts responses of the entire structure to measured or predicted environmental conditions with a hybrid model combining numerical simulations with measurements. While the traditional structural monitoring system focuses on the health condition of typical hot spots, the proposed digital twin may improve structural health awareness of the entire hull structure based on a limited number of sensors.